Pengalaman Ibu Bekerja dan Ibu Tidak Bekerja dalam Membentuk Perkembangan Anak - Mutiara, Yolanda; Maftukhah, Nurul; Agustina, Tasa; Sakilla, Dhea Putri (Jurnal Tematik, 2025)
This study indicates that a mother's employment status (working or not working) has a distinct impact on child development. Children of working mothers tend to exhibit better cognitive development, particularly in problem-solving and critical thinking skills, likely due to more structured stimulation and utilization of external resources. On the other hand, children of non-working mothers tend to have stronger emotional bonds with their mothers, better social adaptability, and higher self-confidence, resulting from more intensive maternal presence at home. Although there are no significant differences in overall behavior, children of working mothers tend to be more independent and responsible, while children of non-working mothers tend to be more compliant.